The Turkish Ordeal: written in “Voluntary” exile, self-translated under ideological embargo - Kürük, Nur Zeynep. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
This study explores the ideological embargo on Halide Edib Adıvar and her self translation of The Turkish Ordeal into Turkish by analyzing the non-translated parts in the English original. Halide Edib wrote the second volume of her memoirs in English, when she was in a “voluntary” exile in England in 1928. However, she did not translate The Turkish Ordeal into Turkish until 1960. When its Turkish version, Türk’ün Ateşle İmtihanı was published in 1962, a considerable amount of the source text was omitted by Edib herself. In this study, these omitted/non-translated parts are examined through a descriptive and comparative textual analysis, in relation to Halide Edib’s self-translation practice by investigating her political and personal position as well as the ideological environment of Turkey between the 1920s and the early 1960s. Halide Edib had a more critical tone in her narration while she was living abroad and writing in English. However, her criticism of Mustafa Kemal Atatürk and some of his politics, her nationalist emphasis on the minority issues and her rather ‘sincere’ personal thoughts have been lost in non-translation. From this perspective, this study asserts that the overall message of Halide Edib’s memoir has changed losing also its critical tone, and turned into a discourse which seems to be supporting or confirming the official state narrative of Turkey. It is also possible to conclude that her representation has remained incomplete in the Turkish context because of the non-translated parts.